ANALISIS IMPLEMENTASI MANAJEMEN SEKOLAH DALAM MENINGKATKAN KINERJA DAN DISIPLIN WARGA SEKOLAH (STUDI KASUS DI UPT SD NEGERI 036410 KM 11) - Muliyanti, Anggi; Situmorang, Elfi Lumongga; Sinaga, Mutiah; Humairoh, Nazwa; Manurung, Tiani Saulina (Jurnal Merah Putih Sekolah Dasar, 2025)
This study examines how school management can improve the performance and discipline of school staff at UPT SD Negeri 036410 KM 11. Using a qualitative case study approach and in-depth interviews, this study reveals the role of the principal as a leader in implementing participatory, transparent, and accountable management functions. The results of the study indicate that clear division of tasks, a culture of discipline through exemplary leadership and motivation, and transparent financial management contribute significantly to increasing work morale and responsibility of school staff. These results emphasize the importance of participatory school management and transformational leadership as effective strategies to improve the quality of basic education.